Income Analysis of Tomato Farming in Wuasa Village, North Lore Sub-District, Poso District - Ryan Suwandih; F. Failurrahman (Manunggal Halim Jaya, 2024)
Tomato (lycopersicum esculetum), is a horticultural commodity from the group of annual tomato fruit types that can be planted in lowlands or highlands. This fruit is a source of vitamins A and C. The purpose of this study was to analyze the income of tomato farming businesses in Wuasa Village, North Lore District, Poso Regency. The method used is data collection techniques by means of observation and interviews with tomato farmers. The data source for this study is primary data. Based on the results of research in Wuasa Village, North Lore District, Poso Regency from farming respondents, the following conclusions were obtained: The income or profit of tomato farmer 1, Mr. Mujito, was Rp16,125,000. While tomato farmer 2, Mr. Rizal, got income and profit of Rp59,500,000. And tomato farmer 3 got income and profit of Rp38,000,000.